2021
DOI: 10.1039/d1qo00413a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model for N-heterocyclic carbene-catalyzed decarboxylation reactions

Abstract: Identifying the special role of N-heterocyclic carbene (NHC) remains to be one of the most important challenges in organocatalysis field. Herein, we proposed a theoretical model for NHC-catalyzed decarboxylation reactions,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Because of the reliability of DFT on the mechanistic studies of organocatalytic reactions, [31][32][33][34] transition metal-catalyzed reactions [35][36][37][38][39] and enzyme-catalyzed reactions, [40] all the calculations were performed with the Gaussian 09 program by using DFT. The geometries of all stationary points were optimized by using the B3LYP [41] density functional and the 6-31G(d, p) [29,42] basis set (denoted as Level 1).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Because of the reliability of DFT on the mechanistic studies of organocatalytic reactions, [31][32][33][34] transition metal-catalyzed reactions [35][36][37][38][39] and enzyme-catalyzed reactions, [40] all the calculations were performed with the Gaussian 09 program by using DFT. The geometries of all stationary points were optimized by using the B3LYP [41] density functional and the 6-31G(d, p) [29,42] basis set (denoted as Level 1).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Early computational studies found that the decarboxylation step has a relatively higher barrier. Recent density functional theory (DFT) studies suggested a relatively low barrier for the decarboxylation step due to the presence of NHC·H + .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the reliability of density functional theory (DFT) in mechanistic studies of organocatalytic reactions, 34–42 transition metal-catalyzed reactions 43–49 and enzyme catalyzed reactions, 50–52 all the calculations were performed using the Gaussian09 53 program using density functional theory. B3LYP 54 -D3 in conjunction with the standard 6-31G(d, p) basis set was employed for all geometry optimizations.…”
Section: Introductionmentioning
confidence: 99%